2014
DOI: 10.1016/j.prevetmed.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the role of Dichelobacter nodosus and Fusobacterium necrophorum load in initiation and severity of footrot in sheep

Abstract: Footrot is an infectious bacterial disease of sheep that causes lameness. The causal agent is Dichelobacter nodosus. There is debate regarding the role of Fusobacterium necrophorum in disease initiation. This research used an observational longitudinal study of footrot, together with quantitative PCR (qPCR) of bacterial load of D. nodosus and F. necrophorum, to elucidate the roles of each species in the development of disease. All feet of 18 a priori selected sheep were monitored for five weeks assessing disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
101
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(120 citation statements)
references
References 41 publications
17
101
2
Order By: Relevance
“…In DD lesions, Firmicutes predominated in superficial and intermediate lesions, whereas Treponema dominated the deeper layers of the DD lesions. 56 Another study based on 16S rRNA gene and fluorescent in situ hybridization (FISH), showed approximately that 50% of the sequences were Treponema-like, 25% were of 59,94 Chytrid infection High Composition is driven by chytrid infections 60,61,95 Fusobacterium necrophorum and the remaining were composed of other bacterial species. 93 In a metagenomic study, using shotgun sequencing, it was reported that cattle with DD had increased relative abundances of Spirochaetes, Bacteroidetes and Proteobacteria, in contrast to healthy feet which were colonized predominantly by Firmicutes and Actinobacteria.…”
Section: Dysbiosis Of the Skin Microbiome Is Associated With Skin Dismentioning
confidence: 99%
See 1 more Smart Citation
“…In DD lesions, Firmicutes predominated in superficial and intermediate lesions, whereas Treponema dominated the deeper layers of the DD lesions. 56 Another study based on 16S rRNA gene and fluorescent in situ hybridization (FISH), showed approximately that 50% of the sequences were Treponema-like, 25% were of 59,94 Chytrid infection High Composition is driven by chytrid infections 60,61,95 Fusobacterium necrophorum and the remaining were composed of other bacterial species. 93 In a metagenomic study, using shotgun sequencing, it was reported that cattle with DD had increased relative abundances of Spirochaetes, Bacteroidetes and Proteobacteria, in contrast to healthy feet which were colonized predominantly by Firmicutes and Actinobacteria.…”
Section: Dysbiosis Of the Skin Microbiome Is Associated With Skin Dismentioning
confidence: 99%
“…The causative agents for this disease are Dichelobacter nodosus and Fusobacterium necrophorum. 94 Several bacterial taxa have been associated with this disease and, based on a 16S rRNA gene study, 59 microbial diversity and richness was greater in tissues from sheep with interdigital dermatitis, the first clinical sign in footrot lesions, than in healthy interdigital areas, or those with a chronic form of footrot (Table 3). This chronic form is known as virulent footrot and results in separation of the hoof horn from sensitive tissue.…”
Section: Dysbiosis Of the Skin Microbiome Is Associated With Skin Dismentioning
confidence: 99%
“…Fusobacterium necrophorum, also a Gram negative bacterium, is attributed to play a role in the initiation of ID prior to D. nodosus infection1, and/or in the exacerbation of footrot lesions once it is established5. Other bacteria such as Treponema have also been detected in footrot cases, but its role in the disease process remains unclear678.…”
mentioning
confidence: 99%
“…It was also observed that in 52 samples in which both the anaerobes were detected, the affected sheep had severe footrot with lesion scores mostly 4 in comparison to other footrot affected sheep in which F. necrophorum was absent or found alone. However [9], reported that F. necrophorum load was higher in feet of sheep with severe footrot. The reason for this could be that F. necrophorum plays vital role in creating anaerobic micro environment necessary for establishment of D. nodosus in the infected claws of sheep.…”
Section: Detection Of F Necrophorum and D Nodosus From Clinical Sammentioning
confidence: 96%